CONTENT OF CALCIUM, PHOSPHORUS AND IRON IN DUCK EGGS WHICH ARE FEED MAGGOT (Hermetia illucens) - Nando Surbakti ,; Dini Julia Sari Siregar , (Journal of Innovation Research and Knowledge, 2024)
This research aims to evaluate the effect of adding black soldier fly larvae (Hermetia illucens) to duck feed on the calcium, phosphorus and iron content of the eggs produced. This study used a non-factorial completely randomized design (CRD) with 4 feed treatments and 5 replications. Egg samples were taken from each experimental unit for analysis. The feed treatments given were: (FP0) 100% commercial feed; (FP1) 75% commercial feed + 25% fresh larvae; (FP2) 50% commercial feed + 50% fresh larvae; (FP3) 25% commercial feed + 75% fresh larvae. The results of the research showed that the treatment of adding fresh larvae to duck feed had a significant effect (P<0.05) on the calcium, phosphorus and iron content of the eggs produced. However, the addition of fresh larvae to the feed produces eggs with a lower average crude protein than 100% commercial feed. Significantly, the addition of Hermetia illucens larvae to duck feed increased the calcium, phosphorus and iron content of the eggs produced. FP2 treatment (50% commercial feed + 50% fresh larvae) produced the highest egg calcium, phosphorus and iron content. The results of this research indicate that black soldier fly larvae (Hermetia illucens) can be used as an effective alternative food source to improve the nutritional quality of duck eggs. The addition of fresh larvae to duck feed significantly increases the calcium, phosphorus and iron content of the eggs produced. Thus, black soldier fly larvae can be a good feed substitute to enrich the nutritional profile of duck eggs